Saturday

April 19, 2014

April 19, 2014

Posted by **Anonymous** on Monday, July 22, 2013 at 9:20pm.

- algebra -
**Chol**, Monday, July 22, 2013 at 10:00pm=24x^6/4x^3- 12^3/4x^3

= 6x^3. -3

**Related Questions**

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

algebra - Did I do this problem the correct way if so is there a shorter way to ...

Math - consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (...

interm. algebra - 12x^2+6 divided by 24x+12 need help

math help - 5) Consider the equations: f(X)= -6x-1 and g(x)=4x^2 Select the ...

algebra - Use polynominal long division to divide -4x^3+24x^2-24x+4 by x^2-5x+1

Algebra - Divide -4x^3 + 24x^2 – 24x + 4 by x^2 – 5x + 1

Maths - is this correct... (3x^2+4x-3)^2-(3x^2-x+2)^2 then is it this (9x^4+24x^...

Math - Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2

Algebra 1 - (2x^3 - x^2 - 24x + 12) divided by (2x - 1)